The heterogeneity of the Mexican lithospheric mantle: Clues from noble gas and CO2 isotopes in fluid inclusions - Sandoval-Velasquez, Andres; Rizzo, Andrea Luca; Aiuppa, Alessandro; Straub, Susanne M.; Gomez-Tuena, Arturo; Espinasa-Perena, Ramon (Frontiers in Earth Science, 2022)
The abundance of mantle-derived rocks and lavas, in combination with its tectonic evolution, render Mexico a perfect laboratory to investigate the chemical and the isotopic heterogeneity of the lithospheric mantle. New data on the composition of noble gases and CO2 in Mexican mantle xenoliths and lavas is reported. Our samples consist of six ultramafic nodules from the Durango Volcanic Field (DVF) and the San Quintin Volcanic Field (SQVF), monogenetic complexes belonging to the Mexican Basin and Range province; and four lavas from the Sierra Chichinautzin (SCN), a Quaternary monogenetic volcanic field located in the Mexican volcanic arc. Ne and Ar isotopes in fluid inclusions reveal mixing between atmospheric and MORB-like fluids (e.g., 40Ar/36Ar < 1,200). DVF and SQVF nodules record low 40Ar/36Ar and 4He/20Ne that confirm the existence of recycled atmospheric-derived noble gases in the local mantle. The averages of the Rc/Ra ratios (3He/4He corrected for atmospheric contamination) measured in Mexican localities are within the MORB-like range: DVF= 8.39 ± 0.24 Ra, SQVF = 7.43 ± 0.19 Ra and SCN lavas = 7.15 ± 0.33 Ra (1σ). With the aim of assessing the isotopic variability of the Mexican lithospheric mantle, the above results were compared with similar data previously obtained from ultramafic nodules found in the Ventura Espiritu Santo Volcanic Field (VESVF), another Quaternary monogenetic volcanic complex belonging the Basin and Range. The higher 3He/4He ratios in DVF relative to those reported for the VESVF and the SQVF are explained as reflecting different ages of mantle refertilization, triggered by the retreating of the Farallon slab (∼40 Ma ago) and associated delamination slab processes. We propose that the DVF mantle was refertilized more recently (<10 Ma ago) than the mantle beneath the SQVF and VESVF (∼40–20 Ma ago). On the other hand, He-Ne-Ar compositions of SCN olivines share similarities with VESVF xenoliths, suggesting a relatively homogeneous lithospheric mantle in central Mexico. Finally, DVF and the SCN samples exhibit δ13C values within the MORB range (comparable to other values previously reported in fluid inclusions and fumaroles from Popocatépetl, Colima—Ceboruco volcanoes). While we explain the MORB-like carbon signatures of the DVF samples as the result of the above-mentioned refertilization process, the SCN signatures likely reflect either (i) trapping of isotopically fractionated CO2 derived from magmatic degassing or (ii) a mantle source unaffected by subduction-related crustal carbon recycling.